Immersive Learning as a Catalyst for Redesigning Instructional Theory and Design - Khalil, Aysha; Younas, Sobia; Akhtar, Syeda Madeeha (Annals of Human and Social Sciences, 2025)
This study explored how veteran instructional designers interpret immersive learning scenarios using traditional models such as ADDIE and Dick and Carey. It focused specifically on Pakistan’s higher education design context. While immersive technologies promise enhanced engagement and presence, existing research rarely examines how design models adapt to these environments. Legacy instructional frameworks assume structured learning sequences and predictable outcomes. Immersive learning disrupts this logic through embodiment, spatiality, and learner-driven paths. A theory-informed qualitative design was used. Fifteen experts participated in scenario-based focus group discussions structured around the ADDIE model. Data were thematically analyzed using NVivo, with dual coding aligned to structured and experiential frameworks. Findings revealed model breakdowns at all ADDIE stages. Designers struggled to analyze learner readiness, sequence open pathways, define content, implement through outdated systems, and assess emergent learning. Participants improvised with constructivist and experiential strategies when traditional models failed. Instructional design models require transformation, not extension. Institutions must revise designer training, immersive infrastructure, and evaluation philosophy.